Molecular characterization of Corynebacterium pseudotuberculosis and development of recombinant vaccine against caseous lymphadenitis - Shahridon, Syafiqah Adilah (2017)
Corynebacterium pseudotuberculosis is a causative agent for caseous lymphadenitis (CLA), a chronic disease that affects mainly small ruminants. The disease is characterized by formation of abscesses, usually in the lymph nodes and occasionally in organs of the infected animals. Caseous lymphadenitis causes great economic loss in goat and sheep industries due to low quality of milk and wool production. Vaccination has been suggested for control of CLA. Currently available commercial vaccines reduce the severity of infection but fail to control the spread of disease. This study was conducted to characterize the various local isolates of C. pesudotuberculosis and to identify the candidates for development of recombinant cells against CLA. Characterization of the surface proteins of C. pseudotuberculosis using sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE) revealed 11 protein bands with two major proteins of 31 kDa and 40 kDa. The minor bands are 152, 84, 75, 69, 67, 61, 54.8, 52, 49, 44 and 25 kDa. Immunoblotting of the surface proteins revealed four immunogenic protein bands at 75, 40, 31 and 25 kDa with the 40 and 31 kDa bands showed intense reaction. Therefore, genes encoding the 31 kDa and 40 kDa surface proteins (SP) of C. pseudotuberculosis were amplified by polymerase chain reaction (PCR) before being cloned in pET32 Ek/LIC vector. The recombinant plasmids, pET32/LIC-SP31 and pET32/LIC-SP40 were successfully transformed into Escherichia coli Nova Blue strain as cloning host. Sequencing analysis showed that both genes were kept in frame with the vector sequence. Sequencing analysis of the nucleotide sequence of the SP 31 kDa showed 98% homology with putative surface anchored protein fimbrial subunit, SpaA gene of C. pseudotuberculosis strain FRC41. Meanwhile SP 40 kDa showed 99% homology with glyceraldehyde-3-phosphate dehydrogenase (GAPDH) of C. pseudotuberculosisstrain FRC41. Both recombinant plasmids were successfully transformed into Escherichia coli strain BL21 (DE3) as expression host. The subsequent SDS-PAGE and Western immunoblot analyses revealed that the expressed fusion proteins of pET32/LIC-SP31 and pET32/LIC-SP40 were approximately 67 kDa and 54 kDa, respectively. In vivo study was carried out to determine the antibody response and protective capacity of the two recombinant cells in goats. Goats were divided into 3 groups before groups 2 and 3 were exposed intramuscularly with the pET32/LIC-SP31 and pET32/LIC-SP40 recombinant cells, respective while group 1 was the unvaccinated control. Serum samples were collected weekly to evaluate the antibody level via enzyme-linked immunosorbent assay (ELISA).Goats exposed to the recombinant cells showed significantly (p<0.05) higher IgG response compared with the unvaccinated group. At the time of challenge with virulent C. pseudotuberculosis, the IgG levels of the vaccinated goats were significantly higher than the unvaccinated goats. Following challenge, abscesses were observed in the lymph nodes of all groups and C. pseudotuberculosis was successfully isolated from the abscesses. This study revealed that surface proteins of C. pseudotuberculosis were immunogenic. Recombinant cells carrying the surface protein were able to induce good humoral response but failed to protect the goats against challenge by live C. pseudotuberculosis. Thus, further studies on the method to enhance the protective capacity of the vaccine are needed considering C. pseudotuberculosis is an intracellular pathogen. Moreover, effective vaccination against CLA needs administration of the vaccine with adjuvant to stimulate both humoral and cell-mediated immunities.